Precocious Puberty: Etiology and Current Treatment - Jihan Alifa Rahma; Adinda Ilsa Maulida; Alma Dyah Perwita; Baiq Ayu Rahmawati; Clara Nadila; Herodya Lajunee Fesmia; Ni Made Utami Wulandari; Zhayyin Palna Rial Novsyaini; Indana Eva Ajmala (Jurnal Biologi Tropis, 2023)
Precocious puberty also known as premature puberty is an abnormal pubertal development that can affect a child's growth and development. The clinical manifestations of precocious puberty are generally diverse and based on etiology are classified into central precocious puberty (GnRH dependent) and peripheral precocious puberty (GnRH independent). The main concern with precocious puberty is that precocious puberty can be a clinical symptom of an underlying serious disease such as a brain tumor, adrenal or gonadal tumor and others. Early identification of etiology plays an important role in prevention, diagnosis, and treatment of this disease. This literature review aims to determine the etiology and current management of precocious puberty. This literature review uses the keywords "Precocious Puberty AND etiology AND treatment" through the National Center for Biotechnology Information (NCBI) and Google Scholar databases. This article uses 11 articles that were used as references in its preparation. In conclusion, it is necessary to know the etiology of precocious puberty using imaging examinations for optimal management and excluding malignant abnormalities. The current treatment for central precocious puberty is GnRH agonists (gold-standard) and surgery in cases of intracranial lesions and peripheral precocious puberty using a combination of androgen antagonists (spironolactone) and aromatase inhibitors (anastrozole, testolactone) and surgery is indicated for gonadal and adrenal tumors. The role of parents is very important in early detection of precocious puberty, because the earlier the therapy, the better the prognosis.